Pengaruh Corporate Governance, Leverage, dan Kualitas Audit Terhadap Manajemen Laba (Studi Empiris Pada Perusahaan BUMN dan Swasta Pada Tahun 2016-2020): The Effect of Corporate Governance, Leverage, and Audit Quality on Profit Management (Empirical Study of State Owned Company and Private Company in 2016-2020 - M. Abdul Rahman; Tony Irawan; Aruddy (Jurnal Aplikasi Bisnis dan Manajemen, 2024)
Background: Earnings management practices are generally carried out by company management to give a good impression to shareholders or investors regarding the company's performance in one reporting period. Earnings management is carried out, generally by recording profits in the company's financial statements, based on the wishes of the parties interested in it, with the intention of showing that the company has posted good performance and has good performance prospects in the future.Purpose: This study aims to examine the effect of corporate governance which consists of the proportion of independent commissioners, audit committees, and managerial ownership, leverage, and audit quality on earnings management in companies in the BUMN and private sectors in 2016-2020.Design/methodology/approach: The data analysis process in this study used panel data regression analysis.Findings/Result: The results of this study indicate that in the BUMN sector the audit committee and leverage variables have a significant effect on earnings management, while in the private sector the managerial ownership, audit committee and leverage variables have a significant effect on earnings management.Conclusion: The conclusion of this research is that the income minimization pattern often occurs in companies in the private sector with 22 distribution points whose motive is tax avoidance management, but the income maximization pattern often occurs in companies in the BUMN sector with 32 distribution points shown whose main motive is political agenda from the managerial level.Originality/value (State of the art): This research objectively examines companies in the State-Owned Enterprises (BUMN) and Private sectors across various types of industries without focusing on a single specific field. Additionally, the research employs a more diverse sampling method compared to other studies, allowing it to address issues more comprehensively. Keywords: earnings management, corporate governance, leverage, audit quality, financial performance, income minimization, income maximization.